2021
DOI: 10.3389/fpsyg.2020.562846
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Better Than Average Effect on Altruism

Abstract: Prior research suggests that most people perceive themselves to be more altruistic than the average population, an observation known as the better-than-average (BTA) effect. Understanding the BTA effect carries significant public health implications, as self-perceived altruism is closely related to altruistic behaviors, which plays a significant role in individual and societal well-being. However, little is known about whether subpopulations with specific sociodemographic profiles are more likely to hold BTA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…social media, texting, or email) and designing telepsychiatry-based interventions (Valente, 2012 ). Public health professionals and social work practitioners shall also implement tailored interventions that serve the needs of individuals from diverse sociodemographic backgrounds (Cha et al, 2018b ; Chu et al, 2010 ; Lindsey et al, 2019 ; Xiao, Wong, Cheng, & Yip, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…social media, texting, or email) and designing telepsychiatry-based interventions (Valente, 2012 ). Public health professionals and social work practitioners shall also implement tailored interventions that serve the needs of individuals from diverse sociodemographic backgrounds (Cha et al, 2018b ; Chu et al, 2010 ; Lindsey et al, 2019 ; Xiao, Wong, Cheng, & Yip, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Szuster, altruistic inspirations have an association with moral values [ 13 ]. As religious teachings stress upon moral values [ 9 ], altruism has a strong link to religion [ 14 ]. Research on regional differences in altruistic tendencies have also identified religion as one of the most important influencing factor [ 15 , 16 ] as has culture [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was an influencing factor for few participants in our study as well. There were no definite gender differences in participant opinions about altruism, although few studies have described females as being more altruistic [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, anger, particularly when directed towards the outgroup, predicts the desire for both verbal and physical outgroup confrontation (Iyer et al, 2007), support for military action against outgroups (Huddy & Feldman, 2011), and decreased intergroup forgiveness (Tam et al, 2007). In a related vein, research on helping and prosocial behaviour revealed that anger decreased intentions to help people in need of assistance (Weiner, 1980; Xiao et al, 2021; Yang et al, 2017). Therefore, it seems interesting to find useful anger-reduction strategies, particularly in a sports fandom context where this emotion is felt by highly identified sports fans following defeat and encourages intergroup tensions (Bagneux et al, 2021; Crisp et al, 2007).…”
Section: Sports Fandom and Helping Behaviourmentioning
confidence: 99%